2021
DOI: 10.1108/heswbl-09-2020-0209
|View full text |Cite
|
Sign up to set email alerts
|

Accounting students' perceptions of work–life balance, accounting career image and intention to pursue accounting careers

Abstract: PurposeThe purpose of this study is to discover the impact of work–life balance on the intention to pursue accounting careers through accounting career image.Design/methodology/approachThe study managed to collect 693 closed questionnaires, using the five-point Likert Scale, from accounting students in several universities in Java, Sulawesi and Kalimantan, as the three most densely populated islands in Indonesia. The research model is analysed using partial least square method as a part of structural equation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…As for education level, very few studies addressed in a specific way its relationship with career shocks, mainly changes related to career choices among working individuals. In fact, most studies focus on students' career choices (Hatane et al. , 2022).…”
Section: Theoretical Foundation Literature Review and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for education level, very few studies addressed in a specific way its relationship with career shocks, mainly changes related to career choices among working individuals. In fact, most studies focus on students' career choices (Hatane et al. , 2022).…”
Section: Theoretical Foundation Literature Review and Research Questionsmentioning
confidence: 99%
“…As for education level, very few studies addressed in a specific way its relationship with career shocks, mainly changes related to career choices among working individuals. In fact, most studies focus on students' career choices (Hatane et al, 2022). Literature revealed that individuals generally experience career shocks during the school-to-work transition (Akkermans et al, 2015).…”
Section: Heswbl 132mentioning
confidence: 99%
“…The professional work can be conducted with strong education in the professional area and other related competencies. Previous studies have shown that students' perception of the accounting profession is influenced by their knowledge in the core area of accounting (Wessels & Steenkamp, 2009;Zyl & Villiers, 2011;Hatane, et al, 2021). The greater the knowledge of accounting that they have, the more efficiently and effectively they can carry out their jobs and tasks (Rajgopal, 2020).…”
Section: Brief Hypothesis Developmentmentioning
confidence: 99%
“…Negative perceptions likely formed in society can block a smart and bright student to choose an accounting major (Mbawuni, 2015). In contrast, Hatane et al, 2022 show that a positive perception of accounting career images will increase the attractiveness of students to pursue the accounting degree. This can open the opportunity for the best students to choose accounting.…”
Section: Introductionmentioning
confidence: 99%